Media Discourse and The Negotiation of Islamic Authority: A Critical Multimodal Analysis of Hajj Cost Reduction Policy in Indonesia - Adha Anggraini; Nur'annafi Farni Syam Maella; Harliantara Harliantara; Idrus Afandi Akbar (JURNAL INDO-ISLAMIKA, 2026)
Media discourse has become a crucial arena in which public policy, religious legitimacy, and state authority are constructed and negotiated, particularly in religiously sensitive policy contexts such as Hajj governance in Indonesia. Despite extensive studies on Hajj administration, limited attention has been given to how media discourse legitimizes policy and reconfigures Islamic authority through linguistic and multimodal representations. This study aims to analyze how media discourse constructs and negotiates Islamic authority in the communication of the Hajj cost reduction policy, identify the discursive and multimodal strategies used to legitimize the policy, and examine their implications for contemporary Islamic governance. Employing a qualitative critical case study, this research analyzes selected online news reports published during the period surrounding the official policy announcement. Data were examined through the integration of Critical Discourse Analysis and Multimodal Discourse Analysis, focusing on lexical choices, actor representation, visual composition, and numerical visualization. The findings show that media discourse legitimizes the policy by framing Hajj cost reduction as ethical responsibility, positioning state institutions as legitimate religious authorities, reinforcing transparency and efficiency through numerical and visual representations, and embedding fiscal policy within the lived religious experience of Hajj. This study contributes to communication and Islamic governance scholarship by demonstrating that policy legitimacy is produced through the interaction of textual, visual, and numerical modes, resulting in a hybrid form of Islamic authority where bureaucratic governance and moral-religious values mutually reinforce one another.